Analisis del proceso de pirolisis para la obtención de combustible a partir de residuos plásticos (2022)
Plastic manufacturing worldwide has increased over the years due to the great use of this material in many fields; its constant demand has resulted in an inadequate use and disposal of this resource due to society's lack of knowledge and environmental education. Over time, this has had negative consequences for the environment, which has led to the depletion of non-renewable natural resources such as oil and the contamination of various ecosystems, mainly the aquatic environment